Evaluating the systematic position of Ehretia asperula Zoll. & Moritzi based on ITS1, matK and trnL-trnF DNA sequences - Thuy Linh Nguyen; Thi Hang Pham; Van Truong Do; Thi Thu Hue Huynh (Vietnam Journal of Science, Technology and Engineering, 2017)
Ehretia asperula, popular as a medicinal herb that has potential on cancer treatment, has a limited research about its phylogeny relationships. With many innovative advancements in molecular biology, it is more easy and reliable to identify the taxonomic position of a species by molecular markers- DNA barcode. In this study, we used three different markers, ITS1, trnL-trnF, and matK, to evaluate E. asperula’s systematic position. Based on ITS1 sequence, E. asperula belongs to clade Ehretia I and is a close relative of E. resinosa. Moreover, ITS1 was suggested to be use as a suitable DNA barcode in order to identify E. asperula.